The Effect Of Sustainability Reporting Practices On The Quality Of CSR Disclosures In Banking In Indonesia - Wiwik SARASWATI; Eko Ganis SUKOHARSONO; Erwin SARASWATI; Arum PRASTIWI (International Journal of Environmental, Sustainability, and Social Science, 2022)
Corporate social responsibility (CSR) has helped produce corporate banking social responsibility activities. However, even so, some aspects of the disclosure still do not meet the quality of reporting. This study aims to analyze the influence of CSR reporting practices and the quality of disclosures on banking companies in Indonesia. This study used as many as 383 samples of banking companies listed on the Indonesia Stock Exchange (IDX) from 2013 to 2021. This study seeks to investigate the use of three CSR reporting practices: stand-alone reports, assurance, and reporting guidelines. The study results show that banking companies have carried out CSR reporting properly and following the Global Reporting Initiative (GRI) standards but have not fully used assurance services to assess the quality of report disclosures. Banking companies in preparing CSR reports do not present the quality of information properly, so the implementation of sustainability reporting practices has not met the criteria. Banking companies meet the obligation to disclose CSR reports to improve performance. GRI disclosures are more likely to be balanced and have comparative capabilities. The results of this study support the increasing use of CSR reporting practices as a useful tool to improve the quality of CSR reporting in Indonesia.